2002
DOI: 10.4049/jimmunol.168.12.6002
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Urease Release by Helicobacter pylori Stimulates Macrophage Inducible Nitric Oxide Synthase

Abstract: Inducible NO synthase (iNOS) expression and production of NO are both up-regulated with Helicobacter pylori infection in vivo and in vitro. We determined whether major pathogenicity proteins released by H. pylori activate iNOS by coculturing macrophages with wild-type or mutant strains deficient in VacA, CagA, picB product, or urease (ureA−). When filters were used to separate H. pylori from macrophages, there was a selective and significant decrease in stimulated iNOS mRNA, protein, and NO2− production with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 32 publications
5
99
0
1
Order By: Relevance
“…2 A related question is whether specific bacterial factors derived from H. pylori play a role in the induction of macrophage apoptosis and whether these factors work through the c-Myc/ ODC pathway. Notably, we have reported that H. pylori LPS is not a significant activator of macrophages (4) but that urease, a major protein product of H. pylori required for colonization of the organism in vivo, is a major inducing factor for inducible NO synthase in macrophages (6). Along these lines, we have found that urease-deficient mutant strains of H. pylori have attenuated ability to induce c-Myc, ODC, and apoptosis, and recombinant urease activates each of these pathways.…”
Section: C-myc In H Pylori-induced Macrophage Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…2 A related question is whether specific bacterial factors derived from H. pylori play a role in the induction of macrophage apoptosis and whether these factors work through the c-Myc/ ODC pathway. Notably, we have reported that H. pylori LPS is not a significant activator of macrophages (4) but that urease, a major protein product of H. pylori required for colonization of the organism in vivo, is a major inducing factor for inducible NO synthase in macrophages (6). Along these lines, we have found that urease-deficient mutant strains of H. pylori have attenuated ability to induce c-Myc, ODC, and apoptosis, and recombinant urease activates each of these pathways.…”
Section: C-myc In H Pylori-induced Macrophage Apoptosismentioning
confidence: 99%
“…Intriguingly, there is a vigorous gastric mucosal immune response, but this fails to eradicate the organism. H. pylori infection induces a chronic lymphocytic response and an innate immune response in neutrophils, monocytes, and macrophages (2)(3)(4)(5)(6)(7)(8). We have reported several strategies by which the bacterium can avoid host innate immunity by altering macrophage responses to the organism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known however, that H. pylori, which is a neutralophile, is able to survive by producing large amounts of the enzyme urease, which catalyzes hydrolysis of urea present in the stomach to yield NH 3 and CO 2 , thus elevating the pH to neutral as necessary for survival (6). It is generally accepted that urea hydrolysis is accomplished by uptake of urea through a proton-gated channel with hydrolysis taking place inside the bacterium and creating a thin neutral layer around the outer surface of the cell (7), although other studies indicate that this crucial enzyme exists on the cell surface (8)(9)(10), or that it is secreted or released (11,12). In addition to its ability to produce urease to elevate pH of its environment, H. pylori further protects itself by swimming through the protective layer of gastric mucus in the stomach and attaching to the epithelial cells beneath, where it can cause inflammation over the course of lifelong infection.…”
mentioning
confidence: 99%
“…pylori i s a d e c l a r e d t y p e I c a r c i n o g e n ( I ARC, 1994 (Boncristiano et al 2003), 3. H. pylori can induce cell proliferation by increasing levels of several cytokines and regulatory molecules, which are involved in tumour formation and cell transformation (Konturek et al 1997;Sakaguchi et al 1999;Keates et al 2001;Gobert et al 2002;Schiemann et al 2002;Wang et al 2002). Current information about regulation mechanism of epithelial tissue by cytokines and regulatory molecules focus an interest mainly on Epithelial Growth Factor (EGF), Transforming Growth Factor (TGF) and NO synthases (NOS) (Gallo et al 1998;Rubin Grandis et al 1998;Sakaguchi et al 1999;Gobert et al 2002;Schiemann et al 2002).…”
Section: H Pylori Induced Carcinogenesismentioning
confidence: 99%